The Effect of High Intensity Interval Training in Different Forms Applied to Combat Athletes on Body Composition and Muscular Strength - İbrahim Orkun Akcan; Latif Aydos; Mustafa Şakir Akgül (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to investigate effects of two different high intensity interval program for 3 weeks on body composition and strength of combat sport athletes. Twenty-nine combat sport athletes (karate, judo, taekwondo, wrestling) (age 21.41±1.50 years) voluntarily participated in this study. Participants were randomly assigned to two groups; Tabata protocol and running based high intensity interval protocol. Both methods were applied to participants 3 days per week for 3 weeks. Body composition, leg strength, back strength and hand grip strength of the participants were measured before and after the application. Mean values, standard deviations and 95% confidence intervals of the variables were calculated. Data normality was verified using Skewness and Kurtosis values. Paired Sample T Test was used to determine intragroup changes while Independent Sample T Test was used to determine intergroup changes. P value was set at p lt;0.05. There was no significant difference between groups during the first measurement (p gt;0.05). No significant change was found in the variables between two measurements. When groups were compared, there was difference in back strength in favour of Tabata group.